(untitled) (Impact: Journal of Transformation, 2022)
The COVID-19 pandemic has had far-reaching impact at individual, household, community, national and international levels. Specifically, the pandemic has adversely affected public participation due to the restrictions of physical meetings and other measures introduced to curb the spread of the virus. This paper sought to document the effects of these restrictions on public participation in the budget-making process by counties in Kenya and to analyse the various strategies they adopted in their conduct of public participation. The study was based in two counties of Kiambu and Kajiado and the respondents were purposively sampled amongst a volunteer group of county government officials as well as members of the public who had participated in budget forums in the financial year 2020/2021. The study engaged 38 respondents who participated in a survey that used questionnaires to collect data as well as 8 key informant interviews using an interview guide as well as Focus Group Discussions. The results of the study show that the COVID-19 restrictions and other public health guidelines had a negative effect on the attendance of the participants; representation/inclusion of participants; cost and size of venues of the meetings; duration of the meetings; mobilisation of participants; moderation/facilitation of the forums and participants’ access to information. The study also found that the two counties had resorted to several strategies to conduct public participation amidst the restrictions including having scaled-down physical meetings, enhanced use of social media, soliciting for written memoranda from members of the public, use of local administrators, employing online platforms as well as using video-conferencing platforms like Zoom and Google Meet. The study recommends that county governments should utilize a combination of strategies to engage with members of the public and invest more in modern information and communication technology to engage with members of the public during various public participation forums.